M. merleau-ponty: fenomenología y naturalización (2010)
The problematic concept guiding this reflection is that set forth, since the publication of Naturalizing Phenomenology (1999) by both defenders and critics of the project aimed at reintroducing the contributions of phenomenology into the research carried out by contemporary cognitive science. The objective is to show that certain aspects of Merleau-Ponty’s phenomenology especially that of his early period, are a valuable contribution for a theory of cognition and provide the bases for a non-reductionist naturalization of phenomenology as the science of consciousness.